Comparative effects of low‐carbohydrate, full‐strength and low‐alcohol beer on gastric emptying, alcohol absorption, glycaemia and insulinaemia in health. Issue 7 (21st March 2022) - Stevens, Julie E.; Jalleh, Ryan J.; Trahair, Laurence G.; Marathe, Chinmay S.; Horowitz, Michael; Jones, Karen L.
Abstract : Aims: The aim of this study was to evaluate the comparative effects of low‐carbohydrate (LC), full‐strength (FS), and low‐alcohol (LA) beer on gastric emptying (GE), ethanol absorption, glycaemia and insulinaemia in health. Methods: Eight subjects (four male, four female; age: 20.4 ± 0.4 years; BMI 22.7 ± 0.4 kg/m 2 ) had concurrent measurements of GE, plasma ethanol, blood glucose and plasma insulin for 180 min on three separate occasions after ingesting 600 mL of (i) FS beer (5.0% w/v, 246 kcal, 19.2 g carbohydrate), (ii) LC beer (4.6% w/v, 180 kcal, 5.4 g carbohydrate) and (iii) LA beer (2.6% w/v, 162 kcal, 17.4 g carbohydrate) labelled with 20 MBq 99mTc‐calcium phytate, in random order. Results: There was no difference in the gastric 50% emptying time (T50) (FS: 89.0 ± 13.5 min vs LC: 79.5 ± 12.9 min vs LA: 74.6 ± 12.4 min; P = .39). Plasma ethanol was less after LA than LC ( P < .001) and FS ( P < .001), with no difference between LC and FS ( P = 1.0). There was an inverse relationship between plasma ethanol at 15 min and GE after LA ( r = −0.87, P < .01) and a trend for inverse relationships after LC ( r = −0.67, P = .07) and FS ( r = −0.69, P = .06). The AUC 0–180 min for blood glucose was greater for LA than LC ( P < .001), with no difference between LA and FS ( P = .40) or LC and FS ( P = 1.0). Conclusion: In healthy young subjects, GE of FS, LC and LA beer is comparable and a determinant of the plasma ethanol response.